2012
DOI: 10.5267/j.msl.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study to determine effective factors on organizational commitment

Abstract: Organizational commitment plays an important role on the success of business units. Many companies rely on their human resources and when some skilled employees leave an organization, there would be a chaos in some organizations especially in small business units. The proposed study of this paper gathers the necessary information from 200 employees who work for custom organization in Iran. The results of factor analysis have indicated there are four factors influencing organizational commitments. The first fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…They concluded that those employees who could get more experience and maintain a good educational background would more likely to stay with a firm than young employees. Azad and Sadeghi (2012) gathered the necessary information from 200 employees who worked for custom organization in Iran. The results of factor analysis indicated there were four factors influencing organizational commitments.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that those employees who could get more experience and maintain a good educational background would more likely to stay with a firm than young employees. Azad and Sadeghi (2012) gathered the necessary information from 200 employees who worked for custom organization in Iran. The results of factor analysis indicated there were four factors influencing organizational commitments.…”
Section: Introductionmentioning
confidence: 99%
“…Azad et al (2013), for instance, determined critical components in agricultural insurance using factor analysis. Azad and Sadeghi (2012) performed an empirical study to determine effective factors on organizational commitment using factor analysis. Abdolvand et al (2012) studied effective factors for the success of tourism industry in Iran using factor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Human resources are the primary component of any organizations and it is important to make any changes within the organizations to increase their commitment. Azad and Sadeghi (2012) indicated four factors influencing organizational commitments. The first factor is associated with cultural factor, the second issues are human resource based factors while the third factor is related to the behavior based factors and finally empowering based factors are the last item.…”
Section: Introductionmentioning
confidence: 99%